Evidências empíricas do efeito da nota fiscal paulista e alagoana sobre a arrecadação estadual - Toporcov, Patrícia Ferreira (2009)
This paper aims at measuring the collection capacity of two Brazilian Tax Programs named Nota Fiscal Paulista (Sao Paulo’s invoice) and Nota Fiscal Alagoana (Alagoas’ invoice), unveiled by Sao Paulo and Alagoas states, with the goal of reduce companies’ fiscal evasion by stimulating individuals to ask for their invoices when purchasing goods. This paper addresses empirically what influences shadow economies, with the intention to determine the driving forces towards a lower fiscal evasion in Brazil. Program results for Sao Paulo show the rise of approximately 20% in the fiscal revenue. Alagoas analysis is inconclusive probably due to short time period enrolled. Our empirical analysis indicates strong evidence that the program has capacity to raise fiscal revenue in approximately 12% in comparison of the beginning of that program. It is important to emphasize that related costs to the implementation of the program with rebate, wages and systems, were not analyzed. Those imply in the reduction of positive outcomes of this program.